Hubungan Status Gizi Ibu Hamil dengan Kejadian Preeklamsia di Puskesmas Sungai Durian Sintang - Della, Hugolin; Fadhilah, Siti; Merida, Yunri (Jurnal Siti Rufaidah, 2025)
Background: Maternal mortality rate (MMR) in Indonesia remains a serious problem, with preeclampsia as one of its main causes. Based on data from Sungai Durian Primary Health Center in 2024, there were 60 cases of preeclampsia (6%) as well as an increasing trend of cases and variations in the nutritional status of pregnant women. Objective: This study aims to determine the relationship between the nutritional status of pregnant women and the incidence of preeclampsia at Sungai Durian Primary Health Center, Sintang. Methods: This is a quantitative research study with a cross-sectional design. Data were collected using observation sheets from medical record data, specifically data on pregnant women with nutritional status and preeclampsia, with a population of 555 pregnant women and a sample size of 232 women. Data analysis was performed using the Spearman Rank test. Results: There were 59 cases (25.4%) of mild preeclampsia and 104 cases (44.8%) of severe preeclampsia. There were variations in the nutritional status of pregnant women: 35 women (15.1%) were undernourished, 132 women (56.9%) had normal nutrition, 25 women (10.3%) were overweight, 24 women (10.3%) had obesity class I, and 16 women (6.9%) had obesity class II. The Spearman Rank test results showed p 0.000 (<0.05), concluding that there is a significant relationship between the nutritional status of pregnant women and the incidence of preeclampsia. Conclusion: There is a relationship between the nutritional status of pregnant women and the incidence of preeclampsia at Sungai Durian Primary Health Center, Sintang.